2018
DOI: 10.1089/neu.2017.5368
|View full text |Cite
|
Sign up to set email alerts
|

Gene Profiling of Nucleus Basalis Tau Containing Neurons in Chronic Traumatic Encephalopathy: A Chronic Effects of Neurotrauma Consortium Study

Abstract: Military personnel and athletes exposed to traumatic brain injury may develop chronic traumatic encephalopathy (CTE). Brain pathology in CTE includes intracellular accumulation of abnormally phosphorylated tau proteins (p-tau), the main constituent of neurofibrillary tangles (NFTs). Recently, we found that cholinergic basal forebrain (CBF) neurons within the nucleus basalis of Meynert (nbM), which provide the major cholinergic innervation to the cortex, display an increased number of NFTs across the pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 87 publications
7
22
3
Order By: Relevance
“…2A). Co-staining of the dendritic marker MAP2 with Cav-1 showed decreased MAP2 expression in the hippocampal CA1 subfield and cortex in PSAPP-SynRFP, similar to that observed in postmortem human brains of patients diagnosed with CTE, tauopathy, and AD [17,18]. In contrast, PSAPP-SynCav1 mice displayed increased hippocampal (Fig.…”
Section: Syncav1 Preserves Mlr-localization Of Cav-1 and Trkb In Hippsupporting
confidence: 78%
See 3 more Smart Citations
“…2A). Co-staining of the dendritic marker MAP2 with Cav-1 showed decreased MAP2 expression in the hippocampal CA1 subfield and cortex in PSAPP-SynRFP, similar to that observed in postmortem human brains of patients diagnosed with CTE, tauopathy, and AD [17,18]. In contrast, PSAPP-SynCav1 mice displayed increased hippocampal (Fig.…”
Section: Syncav1 Preserves Mlr-localization Of Cav-1 and Trkb In Hippsupporting
confidence: 78%
“…There are conflicting results regarding Cav-1 expression levels in the AD brain; while the present study and others have shown decreased Cav-1 protein and mRNA in the AD and neurodegenerative brain [17], Gaudreault et al detected increased Cav-1 protein and mRNA in the hippocampus and frontal cortex of AD brains [46]. It is well known that both astrocytes and microglia express Cav proteins [47][48][49].…”
Section: Discussioncontrasting
confidence: 65%
See 2 more Smart Citations
“…This regulation of intracellular Ca2+ levels makes it an important mediator of learning and memory, and it relies on signal transduction involving extracellular signal-regulated kinase 1/2 (ERK 1/2) and cAMP response element binding protein (CREB) [27]. Recently, Mufson EJ et al [28] reported a decrease in the cholinergic neurotransmitter-related transcript CHRNB2 of neurons in traumatic encephalopathy, which encodes the acetylcholine receptor subunit β2. These findings are consistent with clinical pathology studies demonstrating cholinergicrelated defects in human TBI, including reduced ChAT activity and immunoreactivity, as well as downregulation of vAChT and AChE [29].…”
Section: Nicotinic Receptormentioning
confidence: 99%